DySCo: quantitating associations of membrane proteins using two-color single-molecule tracking. - Dunne, P; Fernandes, R; McColl, J; Yoon, J; James, JR; Davis, S; Klenerman, D (2009)
We present a general method called dynamic single-molecule colocalization for quantitating the associations of single cell surface molecules labeled with distinct autofluorescent proteins. The chief advantages of the new quantitative approach are that, in addition to stable interactions, it is capable of measuring nonconstitutive associations, such as those induced by the cytoskeleton, and it is applicable to situations where the number of molecules is small.